Pre-treatment interleukin-6 levels strongly affect bone erosion progression and repair detected by magnetic resonance imaging in rheumatoid arthritis patients. (8th March 2017) - Kondo, Yasushi; Kaneko, Yuko; Sugiura, Hiroaki; Matsumoto, Shunsuke; Nishina, Naoshi; Kuwana, Masataka; Jinzaki, Masahiro; Takeuchi, Tsutomu
Abstract: Objective. To examine the relationship between MRI structural damage and repair and plasma inflammatory cytokines in patients with RA. Methods. A total of 88 newly diagnosed, untreated RA patients were enrolled. Contrast MRI of the dominant hand and X-rays of the hands and feet were performed at baseline and 1 year later. MR images were evaluated using RA MRI scoring, and X-ray were assessed by the modified total Sharp score. Erosion progression was defined as changes in RA MRI scoring erosion or modified total Sharp score erosion of >0.5. Erosion repair was defined as erosion score changes of less than −0.5. Plasma levels of 10 cytokines were measured by electrochemiluminescence assay. Results. Progression of bone erosion and repair were observed more frequently in MRI than in X-rays (erosion, 52% vs 26%, P < 0.001; repair, 26% vs 15%, P = 0.003, respectively). Baseline IL-6 levels and seropositivity were independent relevant factors for MRI erosion progression, with IL-6 having stronger effect than seropositivity. A receiver operating characteristic curve identified the baseline IL-6 level of 7.6 pg/ml for predicting erosion progression during 1 year, with an area under the curve of 0.82; higher IL-6 levels resulted in more erosion progression. Baseline low IL-6 was also an independent predictor for MRI erosion repair. Conclusion. In newly diagnosed, untreated RA patients, baseline plasma IL-6 levels are responsible for 1-year MRI bone erosion progression and repair.